POSITION OF SCHOOL SUPERVISOR OFFICES IN GOVERNMENT REGULATION NUMBER 57 OF 2021 - Aspandi Aspandi (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2021)
The purpose of this study was to describe the position of school supervisors in PP 57/2021. Thus, the research question posed is how is the position of school supervisors in PP 57/2021? This study uses a qualitative approach with the type of literature study research. The primary data source in this study is Government Regulation number 57 of 2021. This study uses documentation techniques to collect data on the position of school supervisors in PP 57 of 2021. The results show that the position of school supervisors is not accommodated in PP 57 of 2021 concerning national standards. education. Thus, considering the position of school supervisors is very central in the education quality assurance system. So the position of school supervisor must remain and need to be re-stated in the revised Government Regulation 57 of 2021.